The Effects of Interdot Spacing and Dot Size on the Performance of InGaAs/GaAs QDIBSC - Sayeda Anika Amin; Md. Tanvir Hasan; Muhammad Shaffatul Islam (International Journal of Photoenergy)
In0.53Ga0.47As/GaAs-based quantum dot intermediate band solar cells (QDIBSCs) have been designed and optimized for the next generation photovoltaic technology. The wave behavior of charge carriers inside the dot and their barrier have been analyzed with different dot sizes and interdot spacing. The device characteristics such as short circuit current density, Jsc, open circuit voltage, Voc, and conversion efficiency, η, have been evaluated. Based on the behavior of electron wave function, it is found that varying the dot spacing leads to a change in the IB width and in the density of states, whereas varying the size of dots leads to a formation of a second IB. For a fixed dot spacing, two ranges of dot sizes vary the number of IBs in In0.53Ga0.47As/GaAs QDIBSC. Smaller dots of a size ranging from 2 nm to 5 nm form a single IB while larger dots of a size ranging from 6 nm to 9 nm can produce 2 IBs. The efficiency of 2 IBs close to 1 IB suggests that formation of multiple IBs can possibly enhance the device efficiency.